AHNS Series – Do you know your guidelines? Principles of treatment for glottic cancer: A review of the National Comprehensive Cancer Network guidelines. Issue 9 (27th June 2017) - Yesensky, Jessica; Agrawal, Nishant; Bayan, Semirra; Blair, Elizabeth; Portugal, Louis; Chan, Jason; Goldenberg, David; Gooi, Zhen
Abstract: This article is a continuation of the "Do You Know Your Guidelines" series, an initiative of the American Head and Neck Society's Education Committee to increase awareness of current best practices pertaining to head and neck cancer. The National Comprehensive Cancer Network (NCCN) guidelines for primary and adjuvant treatment of cancer of the glottic larynx are reviewed here in a systematic fashion according to stage.